Respuesta :
Let's solve your equation step-by-step.
6(x−1)=9(x+2)
Step 1: Simplify both sides of the equation.
6(x−1)=9(x+2)
Simplify:
(6)(x)+(6)(−1)=(9)(x)+(9)(2)(Distribute)
6x+−6=9x+18
6x−6=9x+18
Step 2: Subtract 9x from both sides.
6x−6−9x=9x+18−9x
−3x−6=18
Step 3: Add 6 to both sides.
−3x−6+6=18+6
−3x=24
Step 4: Divide both sides by -3.
−3x−3=24−3
x=−8
Answer: x= -8
-Hope I helped.
6(x−1)=9(x+2)
Step 1: Simplify both sides of the equation.
6(x−1)=9(x+2)
Simplify:
(6)(x)+(6)(−1)=(9)(x)+(9)(2)(Distribute)
6x+−6=9x+18
6x−6=9x+18
Step 2: Subtract 9x from both sides.
6x−6−9x=9x+18−9x
−3x−6=18
Step 3: Add 6 to both sides.
−3x−6+6=18+6
−3x=24
Step 4: Divide both sides by -3.
−3x−3=24−3
x=−8
Answer: x= -8
-Hope I helped.
Answer: The required solution is x = -8.
Step-by-step explanation: We are given to solve the following equation for x :
[tex]6(x-1)=9(x+2)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To solve the given equation for x, we must take all the terms involving x on one side and the other constant terms on the other side of the equation.
From equation (i), we get
[tex]6(x-1)=9(x+2)\\\\\Rightarrow 6x-6=9x+18\\\\\Rightarrow 9x-6x=-6-18\\\\\Rightarrow 3x=-24\\\\\Rightarrow x=-\dfrac{24}{3}\\\\\Rightarrow x=-8.[/tex]
Thus, the required solution is x = -8.
Otras preguntas
